Heating boilers. Heating boilers with forced draught burners. Specific requirements for the domestic hot water operation and energy performance of water heaters and combination boilers with atomizing oil burners of nominal heat input not exceeding 70 kW Part 6, (23rd August 2019) - British Standards Institution,
No abstract available